Hydrogen production by tailoring the brookite and Cu2O ratio of sol-gel Cu-TiO2 photocatalysts. (October 2017) - Hinojosa-Reyes, Mariana; Camposeco-Solís, Roberto; Zanella, Rodolfo; Rodríguez González, Vicente
Abstract: Cu-TiO2 photocatalysts were prepared by the sol-gel method. Copper loadings from, 1.0 to 5.0 wt % were used. The materials were annealed at different temperatures (from 400 to 600 °C) to study the formation of brookite and copper ionic species. The photocatalysts were characterized by X-ray diffraction, UV–vis, Raman and XPS spectroscopies, H2 -temperature programmed reduction (TPR), N2 physisorption, and SEM–EDS to quantify the actual copper loadings and characterize morphology. The photocatalysts were evaluated during the hydrogen photocatalytic production using an ethanolic solution (50% v/v) under UV and visible radiation. The best hydrogen production was performed by Ti-Cu 1.0 with an overall hydrogen production that was five times higher than that obtained with photolysis. This sample had an optimal thermal treatment at 500 °C, and at this temperature, the Cu2 O and brookite/anatase ratio boosted the photocatalytic production of hydrogen. In addition, a deactivation test was carried out for the most active sample (TiO2 -Cu 1.0), showing unchanged H2 production for three cycles with negligible Cu lixiviation. The activity of hydrogen-through-copper production reported in this research work is comparable with the one featured by noble metals and that reported in the literature for doped TiO2 materials. Highlights: The sol-gel process allows the formation of brookite and Cu2 O oxide. The Ti-Cu 1.0/500 have the highest Cu 1+ /Cu 2+ and optimal brookite/anatase ratio. Cu2 O enhances the H2 production due to correlation between Eg and redox potentials. Ti-Cu 1.0/500 photocatalyst shows the highest H2 production without Cu lixiviation. Cu catalysts represents a cost saving of 124 times in contrast with the noble metals.